2010
DOI: 10.1021/jm1004978
|View full text |Cite
|
Sign up to set email alerts
|

Analogues of (3R)-7-Hydroxy-N-[(1S)-1-{[(3R,4R)-4-(3-hydroxyphenyl)-3,4-dimethyl-1-piperidinyl]methyl}-2-methylpropyl)-1,2,3,4-tetrahydro-3-isoquinolinecarboxamide (JDTic). Synthesis and in Vitro and in Vivo Opioid Receptor Antagonist Activity

Abstract: The synthesis of compounds 6, 7a,b, 8a,b, 9a,b, and 10a,b where the amino -NH- group of JDTic (3) was replaced with an aromatic =CH–, CH2, O, S, or SO group was accomplished and used to further characterize the SAR of the compound 3 class of κ opioid receptor antagonists. All of the compounds showed subnanomolar to low nanomolar Ke values at the κ opioid receptor. The most potent compound was 7a, where the amino -NH- group of 3 was replaced by a methylene (-CH2-) group. This compound had a Ke = 0.18 nM and was… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
24
0

Year Published

2013
2013
2018
2018

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 24 publications
(24 citation statements)
references
References 45 publications
0
24
0
Order By: Relevance
“…The recent termination of the phase 1 clinical trials of JDTic due to undisclosed adverse effects (ClinicalTrials.gov, NCT01431586) has further spurred the search for new, safe and shorter acting KOR-selective antagonists. As discussed above, while several new non-peptide KOR antagonists have recently been reported, including some with finite durations of KOR antagonist activity (Runyon et al, 2010;Peters et al, 2011) or with short residence time in the brain (Grimwood et al, 2011;Mitch et al, 2011) after peripheral administration, reports of orally active KOR antagonists have been limited to only four KOR-selective antagonists: JDTic (Beardsley et al, 2005), an analogue of JDTic (Beardsley et al, 2010), an aminobenzyloxyarylamide (Mitch et al, 2011), and a biphenylsulfonamide (Chang et al, 2011). To date, p.o.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The recent termination of the phase 1 clinical trials of JDTic due to undisclosed adverse effects (ClinicalTrials.gov, NCT01431586) has further spurred the search for new, safe and shorter acting KOR-selective antagonists. As discussed above, while several new non-peptide KOR antagonists have recently been reported, including some with finite durations of KOR antagonist activity (Runyon et al, 2010;Peters et al, 2011) or with short residence time in the brain (Grimwood et al, 2011;Mitch et al, 2011) after peripheral administration, reports of orally active KOR antagonists have been limited to only four KOR-selective antagonists: JDTic (Beardsley et al, 2005), an analogue of JDTic (Beardsley et al, 2010), an aminobenzyloxyarylamide (Mitch et al, 2011), and a biphenylsulfonamide (Chang et al, 2011). To date, p.o.…”
Section: Discussionmentioning
confidence: 99%
“…Unfortunately, this prolonged duration precludes certain key preclinical studies and could potentially impair clinical development. Recently, several new non-peptide KOR antagonists have been reported (Brugel et al, 2010;Runyon et al, 2010;Grimwood et al, 2011;Mitch et al, 2011;Peters et al, 2011;Frankowski et al, 2012), some of which demonstrated shorter durations of KOR antagonist activity (Runyon et al, 2010;Peters et al, 2011) or were detected for relatively short (<8 h) periods in the brain (Grimwood et al, 2011;Mitch et al, 2011). However, activity after p.o.…”
Section: Introductionmentioning
confidence: 99%
“…The reaction mixture was bath sonicated for 5 min to obtain a good dispersion, and then stirred at room temperature overnight. Subsequently, 37% hydrochloric acid (HCl, AnalaR grade, BDH) was added drop-wise until the pH value of the solution reached pH 2 [46]. The mixture was stirred for another 12 hours, then filtered on a 0.45 µm PTFE membrane, and washed with water (3 × 30 mL).…”
Section: Methodsmentioning
confidence: 99%
“…However, the prototypical KOP receptor-selective non-peptide antagonists nor-BNI, 5′-guanidinylnaltrindole (GNTI) and JDTic exhibit exceptionally long activity, antagonizing KOP receptors for weeks after a single dose (Metcalf and Coop, 2005;). This profile could potentially complicate their use as pharmacological tools and as possible therapeutic agents, spurring the search for shorter acting KOP receptor-selective antagonists (Brugel et al, 2010;Runyon et al, 2010;Grimwood et al, 2011;Peters et al, 2011;Frankowski et al, 2012).…”
Section: Introductionmentioning
confidence: 99%